The effect of grazing of various cattle breeds on botanical composition of low-lying pasture in Hortobágy - Kovácsné Koncz, Nóra; Tóth, Katalin; Radócz, Szilvia; Béri, Béla (Acta Agraria Debreceniensis, 2017)
Coenological surveys were conducted in the Hortobágy National Park (Pap-ere and Zám-puszta) in May 2015 and 2016. During the tests,a total of 40 permanent plots were analyzed on grasslands grazed by extensive cattle (Hungarian Grey) and mixed genotype intensive cattle. The presence of plant species, percentages of total coverage of species and vegetation cover were recorded. Two habitat types were chosen according to their moisture content: wet salt marsh meadow (Bolboschoenetum maritimi) and drier salt meadows (Beckmannion eruciformis).We compared the impact of increased number of animals (2016 years) and the low number of animals (2015 years, initial state) and the grazing exclusion on vegetations.We tested: (i) what is the impact of grazing on the vegetation, (ii) how do species composition and vegetation charachteristics differ in the two habitat types (iii) and is there a difference in the impact of different cattle breeds (Hungarian gray, intensive beef cattle) grazing on the grasslands species composition? During the investigation we found, (i) that the greatest number of species was recorded in 2015, on the area that received moderate to intensive grazing (14.3 species per m2). Somewhat the number of species was reduced in 2016 due to more intensive grazing. The control group had the lowest number of species (11.7 species per m2). The undergrass and legumes cover significantly increased on intensive grazed lands. (ii) Our results indicate that the effects of different grazing differ in the two studied habitat types. On the drier grasslands greater number of species were found (16.2 species per m2), oppositely to the wet grassland (11.2 species per m2). The cover of the undergrasses was higher in the drier habitat than in the wet. (iii) The extensive beef cattle left a bigger number of species (16 species per m2) than the intensive beef cattle (11.4 species per m2). The grass cover was more intense on areas grazed by intensive cattle. The absolute and potential weeds cover showed a higher value on areas grazed by Hungarian Grey. Our two-year results suggest that grazing by both extensive and intensive cattle breeds can be a proper tool for the conservation management of alkali grasslands.